Technology News - No. 500 - Using In-Place Stone Stoppings To Direct Air in Underground Stone Mines (The National Institute for Occupational Safety and Health (NIOSH), 2002)
To improve the ventilation of large-opening under-ground stone mines by using stoppings made from stone left in place. Background Underground stone mines typically use large room-and-pillar openings with little ventilation control. Stone miners may be exposed to contaminants that include silica dust, diesel particulate matter (DPM), exhaust gases, nuisance dust, and face shot (blasting) fume gases. The health risks from breathing these fine particles and toxic organic materials are well documented. Although contaminants such as dust or diesel exhaust can be some-what controlled at the source, the escaping contaminants are often diluted and removed from work areas using ventilation with minimal controls. In many cases, current mine ventilation practices use trial-and-error techniques to improve ventilation. The growing realization of the importance of a healthy work environment along with increased regulations will require many stone mines to implement new ways to improve ventilation. In-place stone stoppings are one option. Mine air flows from one point to another because of a pressure differential between those points. This pressure differential is established using a mechanical fan in conjunction with separations (stoppings) between high-pressure (intake) and low-pressure (return) airways. The separation of intakes and returns is an important concept that is used in most other types of mines. Normally, air moves through underground stone mines with minimal control technology. Fans are placed in locations where they are thought to be most beneficial, and intakes are not separated from returns. In a few smaller underground stone mines, proper ventilation can be achieved with a few strategically placed fans. However, as these mines increase in size, moving adequate quantities of air through-out the mine becomes harder, and separation of intakes and returns becomes a problem. Building traditional mine stoppings to separate the intake and return airways in entries with a cross-section area often exceeding 800 ft2 is difficult. The stoppings must be able to withstand both the dynamic pressure from face shots and the static pressures created by the fans. Construction and maintenance difficulties, as well as high costs, are the main factors preventing these traditional mine stoppings from gaining wide acceptance by the stone mining industry.